Identikasi Motivasi Belajar Siswa Terhadap Pembelajaran Kimia Menggunakan Aplikasi Nearpod Berbasis Pbl Dan Chemo Edutaiment - Nova, Nuria; Kriswantoro, Kriswantoro; Asrial, Asrial; Damris, Damris (Universitas Pakuan, 2025)
IDENTIFICATION OF STUDENTS' LEARNING MOTIVATION TOWARDS CHEMISTRY LEARNING USING THE PBL-BASED NEARPOD APPLICATION AND CHEMO EDUTAIMENTThis study aims to identify students' learning motivation in chemistry learning using the Nearpod application integrated with Problem-Based Learning (PBL) and the Chemo Edutainment approach. Chemistry is often considered a difficult subject because the material is abstract, full of calculations, and requires high analytical skills. This condition makes many students less motivated and inactive in the learning process. Therefore, a learning model is needed that can increase student motivation, interest, and engagement through a more interactive and enjoyable learning experience. The research method used is a quantitative method with data collection through a learning motivation questionnaire. The questionnaire instrument covers several important aspects, namely intrinsic motivation, interest in the material, curiosity, confidence in understanding concepts, and student learning efforts during the learning process. The integration of Nearpod in learning allows teachers to present chemistry content digitally through interactive quizzes, experimental videos, simulations, and direct collaboration. Meanwhile, PBL provides opportunities for students to solve authentic problems, and Chemo Edutainment presents educational entertainment elements such as animations and engaging visual experiments. The results show that the use of Nearpod combined with PBL and Chemo Edutainment significantly increases student learning motivation. This is evident in increased active participation, student enthusiasm for each activity, and deeper understanding of concepts. These findings demonstrate that utilizing digital technology and innovative learning methods can be an effective solution for improving motivation and the quality of chemistry learning in schools.